Trichomonas vaginalis Transports Virulent Mycoplasma hominis and Transmits the Infection to Human Cells after Metronidazole Treatment: A Potential Role in Bacterial Invasion of Fetal Membranes and Amniotic Fluid - Tran Thi Trung Thu; Valentina Margarita; Anna Rita Cocco; Alessandra Marongiu; Daniele Dessì; Paola Rappelli; Pier Luigi Fiori (Hindawi Limited, 2018)
Mycoplasma hominis is considered an opportunistic pathogen able to colonize the lower urogenital tract; in females the infection is associated with severe pregnancy and postpartum complications, including abortion, endometritis, preterm delivery, and low birth weight. Molecular mechanisms of pathogenicity and virulence effectors remain poorly characterized. A number of studies in the last decade have demonstrated that M. hominis can establish an endosymbiotic relationship with Trichomonas vaginalis, a urogenital parasitic protozoon, also associated with adverse pregnancy outcomes. Recently, two bacterial genes (alr and goiB) associated with amniotic cavity invasion and a single gene (goiC) associated with intra-amniotic infections and high risk of preterm delivery have been identified in M. hominis isolated from a group of pregnant patients. In this work we demonstrate that a high number of M. hominis intracellularly associated with T. vaginalis have goiC gene, in association with alr and goiB. In addition, we demonstrate that metronidazole treatment of M. hominis-infected T. vaginalis allows delivering viable intracellular goiC positive M. hominis from antibiotic-killed protozoa and that free M. hominis can infect human cell cultures. Results suggest that molecular diagnostic strategies to identify both pathogens and their virulence genes should be adopted to prevent severe complications during pregnancy.